2005
DOI: 10.1526/003601105775012679
|View full text |Cite
|
Sign up to set email alerts
|

Contested Environmental Hazards and Community Conflict Over Relocation*

Abstract: The majority of the literature on contaminated communities indicates that environmental hazards lead to conflict and dissension. In this paper we examine the salient dimensions of conflict and factionalism in a rural Oklahoma community. The community is heavily contaminated from 80 years of commercial mining operations and was one of the first sites designated on the Environmental Protection Agency's Superfund List in 1983. Despite two decades of remediation efforts, the community remains polluted with lead an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 18 publications
0
56
0
3
Order By: Relevance
“…Still, taken together, the lack of significance of these individual-level predictors is surprising, particularly with regard to tenure, exposure (Myers et al 2008), 5 and the presence of children in the home (Fraser et al 2003;Shriver and Kennedy 2005), which have been found previously to influence the decision to remain in or leave one's home. The implication here is that residents' perceptions of their broader community were more influential in the buyout decision than were their experiences of Sandy, or their personal or family characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Still, taken together, the lack of significance of these individual-level predictors is surprising, particularly with regard to tenure, exposure (Myers et al 2008), 5 and the presence of children in the home (Fraser et al 2003;Shriver and Kennedy 2005), which have been found previously to influence the decision to remain in or leave one's home. The implication here is that residents' perceptions of their broader community were more influential in the buyout decision than were their experiences of Sandy, or their personal or family characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…This is not to say that communities are indifferent to the contested threats of pollution-the myriad claims of bodily harm associated with Cancer Alley testifies to that-but it is notably rare for toxic uncertainty to be translated into meaningful legal action or challenges to the compartmentalized geography of this industrialized space. Environmental justice victories in Louisiana and other polluted regions are therefore the exception rather than the rule, and collective inaction is a far more common occurrence (Shriver and Kennedy 2005;Auyero and Swistun 2009;Neumann 2016).…”
Section: The Necropolitics Of Placementioning
confidence: 99%
“…Place attachment is generally defined as having two major constituents: place identity, which refers to residents' self-perception of their identity relative to their surrounding physical environment, and place dependence, which refers to residents' self-perception of the community's potential to address their needs [45,48,49].…”
Section: Literature Reviewmentioning
confidence: 99%